Constructing the meanings of personal pronouns - Langacker, Ronald W (ASPECTS OF MEANING CONSTRUCTION, Radden, Gunter, Kopcke, Klaus-Michael, Berg, Thomas, Siemund, Peter [Eds], Amsterdam, NE: John Benjamins, 2007 pp 171-187, 2007)
The meanings of personal pronouns are described using basic notions of Cognitive Linguistics. Among these notions are subjective vs. objective construal, profiling, grounding, intersubjectivity, paths of mental access, & conceptual blending. Pronouns are situated with respect to other strategies of nominal grounding. It is explained how personal pronouns can be used impersonally, & the meaning of impersonal 'it' is characterized. Special attention is devoted to 'I' & 'you'. Their abstracted conceptual meanings invoke very basic cognitive models pertaining to the ground, a speech event, & subject vs. object of conception. With these models as inputs, the pronouns' meanings are constructed through successive levels of blending. The crucial factor is intersubjectivity. Figures, References. Adapted from source document